Nonlinear system identification using heterogeneous multiple models - Orjuela, Rodolfo; Marx, Benoît; Ragot, José; Maquin, Didier (Zielona Góra: Uniwersytet Zielonogórski)
Multiple models are recognised by their abilities to accurately describe nonlinear dynamic behaviours of a wide variety of nonlinear systems with a tractable model in control engineering problems. Multiple models are built by the interpolation of a set of submodels according to a particular aggregation mechanism, with the "heterogeneous multiple model" being of particular interest.
Keywords: nonlinear system identification; multiple models; heterogeneous submodels